HistoInformatics2021: The 6th International Workshop on Computational History - Sumikawa, Yasunobu; Ikejiri, Ryohei; Doucet, Antoine; Pfanzelter, Eva; Hasanuzzaman, Mohammed; Dias, Gael; Milligan, Ian; Jatowt, Adam (2021 ACM/IEEE Joint Conference on Digital Libraries (JCDL), 2021)
This paper discusses HistoInformatics2021 workshop (the 6th International Workshop on Computational History) held in conjunction with the JCDL2021 conference. This is the 6th installment of the workshop series devoted to the interaction between Computer Science and History. This interdisciplinary initiative is a response to the growing popularity of Digital Humanities, particularly in historical research, and an increased tendency to apply algorithms and computer techniques for fostering and facilitating new research methods and tools in the Humanities.